التجارة الإلكترونية وآثارها على اقتصاديات الأعمال العربية - يحياوي، نعيمة Yahiawi, Naimah; يوسف، مريم Yousuf, Mariam (جامعة قاصدي مرباح - ورقلة, 2017)
هدفت الدراسة إلي تسليط الضوء علي ظاهرة التجارة الإلكترونية وأهميتها واثارها علي نواحي الحياة المعاصرة لاسيما الجوانب الاقتصادية منها، وكذلك مناقشة أبرز التحديات والمعوقات التي تقف أمام تطور التجارة الإلكترونية، واستعراض أهم المجالات التي يؤمل من البلدان العربية أن تستفيد من تطبيقات التجارة الإلكترونية فيها. وقد أظهرت نتائج الدراسة الأهمية البالغة لهذه الثورة المعلوماتية وتطورها السريع، وآثارها المستقبلية المحتملة على إعادة تشكيل الهياكل الاقتصادية التقليدية. وقد أوضحت الدراسة العديد من المعوقات والتحديات أمام هذه الدول والتي ينبغي العمل علي تذليلها في سبيل الإفادة من تطبيقات التجارة الإلكترونية لما لها من الآثار الإيجابية على مختلف قطاعاتها الاقتصادية. كما أشارت الدراسة إلى العديد من المجالات والقطاعات المختلفة التي يمكن لهذه الدول أن توظف تقنية المعلومات والتجارة الإلكترونية فيها لتفعيلها وتطويرها. وتوصلنا في الأخير لبعض الاقتراحات التي نراها مناسبة لتسهيل تطبيق هذا النوع من التجارة في الدول العربية. This study aimed to shed light on the phenomenon of electronic commerce and its importance and its effects on aspects of contemporary life, particularly the economic aspects of them, as well as discuss the key challenges and obstacles that stand in front of e-commerce development, and review of the most important areas in which it is hoped Arab countries to take advantage of e-commerce applications in it. The results showed the critical importance of this information revolution and its rapid development, and its implications for potential future restructuring on traditional economic. The study revealed many obstacles and challenges to these countries, which should work on overcoming them in order to benefit from e-commerce applications because of their positive effects on various economic sectors. The study also noted a number of areas and sectors that can be for these countries to employ information technology and electronic commerce in which to activate and develop. We reached at last some of the proposals that we see an opportunity to facilitate the application of this type of trade in Arab countries.
Keywords: المعاملات الإلكترونية -- التجارة الخارجية -- الوطن العربي -- التنمية الاقتصادية